2020
DOI: 10.3390/cancers12040983
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Immunity Is Not Essential for Radiation-Induced Heart Dysfunction but Exerts a Complex Impact on Injury

Abstract: While radiation therapy (RT) can improve cancer outcomes, it can lead to radiation-induced heart dysfunction (RIHD) in patients with thoracic tumors. This study examines the role of adaptive immune cells in RIHD. In Salt-Sensitive (SS) rats, image-guided whole-heart RT increased cardiac T-cell infiltration. We analyzed the functional requirement for these cells in RIHD using a genetic model of T-and B-cell deficiency (interleukin-2 receptor gamma chain knockout (IL2RG −/− )) and observed a complex role for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 77 publications
(134 reference statements)
0
1
0
Order By: Relevance
“…For example, Schlaak et al [ 8 ] summarise current state-of-the-art preclinical models of radiation-induced cardiac toxicity, describing the progress in experimental irradiation techniques from whole thorax exposures to those using small animal IGRT. Using an interleukin-2 receptor gamma chain knockout (IL2RG −/− ) rat model of T- and B-cell deficiency with image-guided whole-heart exposures, the group investigated the role of acquired immunity radiation-induced heart dysfunction [ 9 ]. Their study showed that IL2RG deficiency protects from cardiac hypertrophy, but contributes to cardiac dysfunction, highlighting the complex roles for adaptive immune cells in cardiac injury that vary depending on clinically relevant factors including dose, fractionation, sex, and genetic background.…”
mentioning
confidence: 99%
“…For example, Schlaak et al [ 8 ] summarise current state-of-the-art preclinical models of radiation-induced cardiac toxicity, describing the progress in experimental irradiation techniques from whole thorax exposures to those using small animal IGRT. Using an interleukin-2 receptor gamma chain knockout (IL2RG −/− ) rat model of T- and B-cell deficiency with image-guided whole-heart exposures, the group investigated the role of acquired immunity radiation-induced heart dysfunction [ 9 ]. Their study showed that IL2RG deficiency protects from cardiac hypertrophy, but contributes to cardiac dysfunction, highlighting the complex roles for adaptive immune cells in cardiac injury that vary depending on clinically relevant factors including dose, fractionation, sex, and genetic background.…”
mentioning
confidence: 99%